Molecular evaluation of quercetin effects in a murine model of giant cell tumor of bone: an in vivo pilot study: Quercetin effect in a GCT murine model - Monroy-Quiroz, Dalia Lizbeth; Luna-Angulo, Alexandra Berenice; Galicia-Canales, Brandon Eduardo; Sánchez-Chapul , Laura; Hernández-González , Olivia; Aguilar-Gaytán, María del Rocío; Santamaría-Olmedo, Mónica Guadalupe; Hidalgo-Bravo , Alberto; Couder-García, Beatriz del Carmen; Lara-Hernández , Gabriel; Estrada-Villaseñor , Erendira Georgina; Landa-Solís, Carlos (Cellular and Molecular Biology, 2025)
Quercetin, a flavonoid derived from plant sources, has been extensively studied for its numerous biological properties, particularly its potential antitumor action against various malignant neoplasms. In our experience with a giant cell tumor of bone cell line (TIB-223), we demonstrated that quercetin has the ability to induce apoptosis via caspase-3. Therefore, this study aimed to evaluate molecular markers for apoptosis, necrosis, and cell proliferation in a murine model of giant cell tumor of bone, to determine whether the behavior reported for quercetin in 2D remains consistent in a 3D in vivo tumor model. Tumor constructs based on TIB-223 cells were implanted into athymic mice, and two weeks post-implantation, the mice were orally administered quercetin at a concentration of 100 mg/kg body weight once a day for two weeks. The control group received only 200 µL of the vehicle. Our results demonstrate the activation of two cell death pathways in the implanted tumors: apoptosis, via Caspase-8 to Caspase-3 activation, and necroptosis, via RIPK1. No significant effect on cell proliferation was observed, as PCNA expression remained unchanged. Our results suggest that quercetin may induce specific mechanisms of cell death without significantly altering cell proliferation in the tumor model induced in mice.